THE EVALUATION OF AVOCADO (Persea americana Mill.) MATURITY LEVEL USING IMAGE PROCESSING TECHNOLOGY - Fenny Aprilliani; Dheni Atmiasih; Andika Ristiono (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
The purpose of this research was to determine the relationship between the maturity level of avocado and color changes using simple device such as smartphone camera. Avocado with 3 different maturity level A1:<80%, A2:80-85%, and A3:>85% were collected from local farmer in Bandungan, Central Java. The quality evaluation was carried out on 99 avocado (weight of 366±16 g) which included the evaluation of mass loss (%), firmness (kg/mm2), total soluble solids (°brix), and color changes (picture of fruit were taken using smartphone camera and analyzed using Photoshop CC 2019 from Adobe and converted into HSI values). The data were analyzed using two-factorial completely randomized design (CRD) with factor design are the level of maturity and storage time of the avocado. The results indicated that the maturity level were significantly different (p≤0.05) for mass loss, firmness and total soluble solids (TSS) of avocado during storage. The relationship between maturity level and color changes shows the MAPE (mean absolute percent error) value for hue, saturation, intensity ranges between 3,31-6,11%; 11,12-15,79%, and 6,10-6,49% with the light intensity of 527,77 lux. The results indicate that the image processing on smartphone camera is able to describe the level of maturity based on the color changes of avocado during storage with the same treatment conditions.